2019
DOI: 10.3390/ijerph16122205
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Phylogenetic Analysis of Campylobacter Species Isolated from Paediatric Stool and Water Samples in the Northwest Province, South Africa

Abstract: Antibiotic-resistant Campylobacter could adversely affect treatment outcomes, especially in children. We investigated the antibiotic susceptibility profiles, virulence potentials and genetic relatedness of Campylobacter spp. from paediatric and water samples in the North West Province, South Africa. Overall, 237 human and 20 water isolates were identified using culture and real-time polymerase chain reaction (PCR). The antibiotic susceptibility profiles were determined using the disk diffusion method. Gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
29
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 95 publications
12
29
2
2
Order By: Relevance
“…Multiple antibiotic resistance genes were highly detected in most of the isolates (Table 6), and this is in agreement with the multiple phenotypic resistance profiles displayed by the isolates (Table 5). Multiple resistance genes in the Campylobacter isolates were detected, and our results are in agreement with the reports of Chukwu et al [74] and Wieczorek et al [91]. There was a high rate of detection of resistance genes in chloramphenicol (catll (91.78%)), tetracycline (tetA (68.82%)), ciprofloxacin (gyra (61.76%)), ampicillin (ampC (55%)), gentamycin (aac(3)-IIa (aacC2) a (40.98%)), and tetracycline (tetM (38.71%) in the Campylobacter isolates.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Multiple antibiotic resistance genes were highly detected in most of the isolates (Table 6), and this is in agreement with the multiple phenotypic resistance profiles displayed by the isolates (Table 5). Multiple resistance genes in the Campylobacter isolates were detected, and our results are in agreement with the reports of Chukwu et al [74] and Wieczorek et al [91]. There was a high rate of detection of resistance genes in chloramphenicol (catll (91.78%)), tetracycline (tetA (68.82%)), ciprofloxacin (gyra (61.76%)), ampicillin (ampC (55%)), gentamycin (aac(3)-IIa (aacC2) a (40.98%)), and tetracycline (tetM (38.71%) in the Campylobacter isolates.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the high occurrence rate of the cadF (37.25%) gene and the lower prevalence of the flaA (1.96%) gene were detected in the Campylobacter isolates from meat samples, and these results are akin with the reports of Andrzejewska et al [77] and Ripabelli et al [78]. Our results also corroborated the report of Chukwu et al [74], who also detected the cadF gene in Campylobacter strains isolated from water and paediatric stools. The ciaB gene was screened for but was not detected, and our findings are contrary to the reports of Melo et al [79], Melo et al [80], and Zhong et al [81] who reported high detection rates of the ciaB gene in meats and in retailed food samples.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Genus-and species-specific primers were used for the identification of Campylobacter together with the cycling conditions have previously been described [101,102]. Additionally, the identification of Arcobacter to the genus level and the simultaneous identification of A. butzleri, A. cryaerophilus and A. skirrowii was as previously described by [103].…”
Section: Genomic Dna Extraction and Pcr Identification Of Arcobacter mentioning
confidence: 99%
“…Isolates that harboured the mdh gene were tested for the presence of eight VGs-eaeA (EPEC/EHEC), eagg (EAEC), ipaH (EIEC), ST and LT (ETEC), stx1, stx2 and flicH7 (EHEC)-as previously described [106,107]. All the PCR assays included a positive control consisting of DNA from a reference strains obtained from the Microbiology Laboratories of the Natural Resources and the Environment (NRE) and CSIR, as well as previously characterised by Abia et al [101]. A reaction mixture void of template DNA was also included in each PCR assay as a no template control.…”
Section: Dna Extraction and Detection Of E Coli Virulence Genes (Vgsmentioning
confidence: 99%